Charge storage properties of a alpha-MoO3/carboxyl-functionalized single-walled carbon nanotube composite electrode in a Li ion electrolyte - Mendoza-Sanchez, B; Grant, P (2013)
A facile, cost-effective and scaleable method is presented for the fabrication of thin film α-MoO3/SWCNT-COOH composite electrodes with a high charge storage capacity in LiClO4/propylene carbonate in a 1.5-3.5 V (versus Li/Li+) working electrochemical window. α-MoO3 nanobelts were synthesized using an established hydrothermal method and composite thin film electrodes incorporating interwoven single walled carbon nanotubes as an electrical conductive additive within a network of α-MoO3 nanobelts were manufactured by spray deposition. The composite electrode showed a maximum charge storage/capacitance of 697.7 C g-1 (193.8 mAh g-1)/ 348.7 F g-1 at 0.1 mV s-1 (per unit mass of composite electrode) with a contribution to charge storage from capacitive and diffusion controlled processes of 443 C g-1 and 463.2 C g-1 (per unit mass of α-MoO 3), respectively, which is comparable to charge storage attained by electrodes manufactured by more costly and non-scaleable templating methods previously reported. Cyclic voltammetry showed capacitances of 167 F g -1 and 75 F g-1 at 10 mV s-1 and 50 mV s -1, respectively, suggesting a potential application as electrochemical capacitor electrodes of moderate power densities. On the other hand, a charge storage of 697.7 C g-1 (193.8 mAh g-1) attained at 0.1 mV s-1, and a capacity of 596.8 mAh g-1 achieved at 10 mA g-1 in galvanostatic charge-discharge experiments supports a potential application of α-MoO3 as a Li-ion battery cathode. © 2013 Elsevier Ltd. All rights reserved.